2017
DOI: 10.1155/2017/1019461
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of Dielectric Properties in Fluid Saturated Artificial Shales

Abstract: High dielectric contrast between water and hydrocarbons provides a useful method for distinguishing between producible layers of reservoir rocks and surrounding media. Dielectric response at high frequencies is related to the moisture content of rocks. Correlations between the dielectric permittivity and specific surface area can be used for the estimation of elastic and geomechanical properties of rocks. Knowledge of dielectric loss-factor and relaxation frequency in shales is critical for the design of techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In a study by Beloborodov et al 15 they concluded that at high frequencies (above 10 MHz) real relative permittivity will show a different linear trend with porosity in fresh water and brine saturated samples. The showed that salinity and cation composition of the pore fluid have a negligible effect on dielectric measurements at high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Beloborodov et al 15 they concluded that at high frequencies (above 10 MHz) real relative permittivity will show a different linear trend with porosity in fresh water and brine saturated samples. The showed that salinity and cation composition of the pore fluid have a negligible effect on dielectric measurements at high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the decrease in the dielectric constant with increase in frequency could be attributed to the contribution of various effects, such as electronic polarization (occurs at frequencies up to 10 13 kHz), ionic polarization (up to 10 10 kHz), dipolar polarization (up to 10 7 kHz) and space-charge polarization (up to 10 2 kHz) [ 55 , 56 ]. Higher values of dielectric constant at low frequency are due to the contribution of all the various types of polarizations in the capacitors.…”
Section: Resultsmentioning
confidence: 99%
“…As Figure 7 demonstrates, the majority of published kaolinite compaction curves document 17-25% total porosity at 50 MPa effective vertical stress [23,26,[55][56][57][58][59][60][61][62][63]. The coarser kaolinite grains were more susceptible to compaction (more compressible) than the finer kaolinites.…”
Section: Inconsistencies In Published Ncts For Pure Kaolinite and Bin...mentioning
confidence: 99%
“…The second inconsistency was found in recognizing maximum compaction in argillaceous deposits. A (majority) group of experimental studies showed that the highest compaction level and maximum porosity loss could be identified for brine-saturated quartz-clay mixtures with 20-40% kaolinite content (and 60-80% quartz) [26,55,59,[64][65][66][67][68][69][70][71]. These experimental works have reported a total porosity of around 12% at 50 MPa effective vertical stress for such mixtures.…”
Section: Inconsistencies In Published Ncts For Pure Kaolinite and Bin...mentioning
confidence: 99%
See 1 more Smart Citation